2017
DOI: 10.1016/j.nbscr.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged day length exposure improves circadian deficits and survival in a transgenic mouse model of Huntington's disease

Abstract: Prolonged day length exposure improves circadian deficits and survival in a transgenic mouse model of Huntington's disease, Neurobiology of Sleep and Circadian Rhythms, http://dx. AbstractThe circadian disruption seen in patients of Huntington's disease (HD) is recapitulated in the R6/2 mouse model. As the disease progresses, the activity of R6/2 mice increases dramatically during the rest (light) period and decreases during the active (dark) period, eventually leading to a complete disintegration of rest-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…As seen previously under DD, with age R6/2 mice exhibited a progressively shorter period length than was seen in WT mice (Wood et al, 2013;Ouk et al, 2017). In mice under DD at 12-13 weeks of age, there was a main effect of genotype on period length (F (1,32) ϭ 16.2; p ϭ 3E-4 w ), amplitude of rhythms (F (1,32) ϭ 14.41; p ϭ 0,0006 x ), and activity counts (F (1,32) ϭ 21.43; p ϭ 6E-5 y ), with all these parameters significantly decreased in R6/2 mice compared with WT mice (Fig.…”
Section: Entrainment To Constant Light and Constant Darkness In R6/2 supporting
confidence: 68%
See 4 more Smart Citations
“…As seen previously under DD, with age R6/2 mice exhibited a progressively shorter period length than was seen in WT mice (Wood et al, 2013;Ouk et al, 2017). In mice under DD at 12-13 weeks of age, there was a main effect of genotype on period length (F (1,32) ϭ 16.2; p ϭ 3E-4 w ), amplitude of rhythms (F (1,32) ϭ 14.41; p ϭ 0,0006 x ), and activity counts (F (1,32) ϭ 21.43; p ϭ 6E-5 y ), with all these parameters significantly decreased in R6/2 mice compared with WT mice (Fig.…”
Section: Entrainment To Constant Light and Constant Darkness In R6/2 supporting
confidence: 68%
“…While our Per1 light-induced expression data support previous findings that the molecular machinery of the SCN is intact, they also indicate that retinal dysfunction is unlikely to be the sole cause of dysrhythmia in R6/2 mice. In support of this suggestion, previous studies have shown that R6/2 mice respond to bright light (Cuesta et al, 2014), jet lag (Wood et al, 2013), and photoperiod length variation (Ouk et al, 2017). This raises the possi-bility that the involvement of downstream areas of the brain innervated by the SCN causes the disruption of the behavioral response to the phase-delaying light pulse.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations